Intravesical BCG: Possible Protective Impact Against COVID-19 in NMIBC Patients - Gabriel GLUCK; B. RADU; Angelica IONESCU; A. BOAR; Ioanel SINESCU (Modern Medicine)
Purpose: To determine the incidence of COVID 19 in a series of registered patients with non-muscle invasive bladder cancer, treated by TUR-BT and intravesical BCG. Patients and method: We analysed 127 patients with nonmuscle invasive bladder cancer, in the medium/high risk group, registered between 2001-2020. The patients and families have been contacted by phone. In this interval, 32 patients deceased (cardiovascular pathologies, non-urologic neoplasia, tumour progression), 95 patients are still alive, 24 women and 71 men. The average age was 61.7 (16-86), the majority being over 50, included in the high-risk group for COVID-19. The patients were resected endoscopically and received a cytostatic instillation within the fi rst 6 hours. Reresection of the tumour bed was practiced in pT1 patients. The adjuvant treatment with BCG was used in the induction form at each relapse and maintenance (22 patients), respectively. Until 2005, we used the local strain (Cantacuzino Clinical Institute), after that, the strain from Bulgaria (Calgevax) and Medac (Germany). Results: 95 patients are still alive. Tumour relapses were registered in 34 patients. 3 patients registered tumour progression, resolved through radical cystectomy (2) and irradiation. In 3 cases, upper tract urothelial tumours were registered (nephroureterectomy with perimeatic cystectomy). 63 patients underwent induction treatment, while 22 underwent maintenance treatment. Complications: Intolerance to BCG in 4 patients, BCG cystitis in 5 patients, arthritis in 1 patient, septic status in 2 patients. In the analysed batch of patients, no COVID-19 cases have been registered. Conclusions: It appears that the intravesical administration of BCG represents an immunologic booster (confirmable through PPD), resulting in a reduction of the COVID-19 infection incidence.